Dosimetric evaluation of 3D-printed polylactic acid (PLA) anthropomorphic radiotherapy head phantom using gafchromic EBT-XD films, OSLD NanoDot and TLD-100 - Noor Nabilah Talik Sisin; Nur Emirah Mohd Zain; Nor Arina Isamail; Reduan Abdullah; Muhammad Afiq Khairil Anuar; Nur Hamizah Mohd Zainudin; Ahmad Bazlie Abdul Kadir; Ashrani Aizzuddin Abd Rahni; Wan Nordiana Rahman; Aml Almutery; Raizulnasuha Abd Rashid (Penerbit Universiti Kebangsaan Malaysia, 2025)
Recently, additive manufacturing or 3-dimensional (3D) printing has been utilized to create low-cost and customized radiotherapy phantoms for quality assurance and radiation dosimetry. In this study, the head phantom was fabricated by scanning a standard RANDO® head phantom using a Kinect® Xbox 360® and printed using polylactic acid (PLA) with 100% infill. The 3D-printed anthropomorphic head phantoms underwent CT simulation, treatment planning, and treatment delivery, similar to the patient setup in radiotherapy with a whole brain target. Irradiation of the phantoms were delivered with a single fraction of 400 cGy using 6 MV photon beam energy. The absorbed dose was measured with three dosimeters: GafChromic EBT-XD film, TLD-100, and OSLD NanoDot. Gamma analysis of EBT-XD films indicated a 30% dose difference for the irradiation’s pass rate of 3D printed head phantom and RANDO® phantom compare to TPS dose calculation. TLD’s measurement of the 3D printed phantom resulted in 99% similarity to the TPS calculation and RANDO® phantom TLD’s results. Meanwhile, the percentage dose difference between OSLD reading of 3D printed phantom and TPS calculation was 8.1%. Therefore, this study demonstrates the feasibility of the 3D-printed head RP as an alternative phantom to RANDO® head RP. Further improvement in the phantom design details might enhance the dosimetry outcome and accuracy.